Letter - Stolz, George
021-0077-001 INTERNATIONAL FEDERATION OF TRADE UNIONS TELEGRAMS: INTERFED-PARIS TELEPHONE: INVALIDES 43-88 AFFILIATED COUNTRIES: ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY PALESTINE POLAND ROUMANIA [ROMANIA] SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA St/G. 9, AVENUE D'ORSAY, PARIS-VIIe EXECUTIVE COMMITTEE: President W.M Citrine, Great Britain; Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France Corn. Mertens, Belgium; R Tayerle, Czechoslovakia; General Secretary: W Schevenels. 4th March, 1938. Letter Finances No. 21 Mr. Parkin, T.U.C. General Council Transport House Smith Square London Dear Mr. Parkin, I asked the CWS Bank in London to transfer to you the amount of £100 (a hundred pounds sterling) which I will need for our Conference to be held next week in London. I should be glad if you would keep it for me and thank you in advance for your kindness. Yours fraternally, G. Stolz, Assistant Secretary. 292/946/21/77